Detecting and improving feature lines on polygonal meshes - Toni. (2013)
Polygonal mesh is the collection of vertices, edges and surfaces that defines the shape of a 3D object. The feature lines in the object are the curves on the surfaces of 3D object that may be a few strokes of lines which can be used to define the prominent characteristic of the objects. In short, they are the set of loci of points where the largest value of principal curvature takes a positive maximum or negative minimum along its corresponding curvature lines. Thus, their definition involves third and fourth order surface derivative which often result in unpleasantly edgy, rough and overly sharp feature line due to high distortion ratio to unwanted surface noise by third order derivative. Since reliable computation of feature lines in polygonal meshes are key to many methods in geometric modelling and computer graphics, this project aim to create a dependable methods to compute fast, stable and visually pleasing feature lines.